The Vatican in the family of nations diplomatic actions of the Holy See at the UN and other international organizations in Geneva - Tomasi, Silvano M. (Cambridge University Press, 2017)
Machine generated contents note: Methodological note; Abbreviations and acronyms; Preface: the Holy See's diplomatic mission in today's world H. E. Pietro Parolin; 1. The human person at the center of fundamental rights and protagonist of development; 2. Freedom as the foundation of human relations and social coexistence; 3. The economy as a means, not an end; 4. The quest for peace; 5. Solidarity with all humanity; 6. People on the move: the challenge of the XXI century; Conclusions: A beacon of inspiration for the family of nations Antonio Manuel de Oliveira Guterres; Index; Bibliography
Title from publisher's bibliographic system (viewed on 30 Aug 2017)
Keywords: Vereinte Nationen; Katholische Kirche -- Sancta Sedes; Geschichte 2000-2015; Internationale Politik; Diplomatie; Internationale Organisation; Außenpolitik; Vatikanstadt; Genf; Quelle